Analisis Risiko dan Proses Manajemen Risiko pada Bank Syariah - Fitriana, Alya Nabila; Yazid, Muhammad (Universitas Islam Negeri Sunan Kudus, 2023)
Islamic banks as financial institutions certainly also have various risks, these risks can be in the form of financing risk, agent risk, and so on. Risk management is very necessary in financial institutions, especially in Islamic banking because risk management can minimize losses that are expected to occur in the future and risk management can provide information to the managers of Islamic banks to make good and appropriate decisions so that the management of Islamic banks will be getting better and Islamic banks are able to increase their competitiveness. This study uses a descriptive qualitative method using literature studies and documentation techniques. The data was obtained from various kinds of written literature that had been made before regarding various risks and how to manage risk in Islamic banks. There are several risks to Islamic banks, including risks to financing and agents. The process of risk management in Islamic banks can be carried out by implementing several steps, namely by identifying risks, measuring risks, monitoring risks, and controlling risks. To make it easier for Islamic banks to minimize risk, DPS was formed. DPS is an institution or board whose job is to oversee the operational activities of Islamic banks with the aim that Islamic banks can run in accordance with Islamic principles and to minimize fraud and misappropriation of funds in Islamic banks.